Notes on the Cyrtopsis Bey-Bienko, 1962 (Orthoptera: Tettigoniidae: Meconematinae) with description the female sex of Cyrtopsis robusta Liu & Zhang, 2007 - Pan, Yangyang; Bian, Xun (Zootaxa, 2023)
This paper provides morphological illustrations of four species of Cyrtopsis including two holotypes. Based on the new collections deposited in Guangxi Normal University, the previously unknown female sex of Cyrtopsis robusta Liu & Zhang, 2007 is described and illustrated.